Application of palladium nanoparticle supported organo-kaolinite for 4-chloro-2-nitroaniline catalytic reduction and electrochemical detection. (9th May 2022) - Mbiagaing, Cyrille Djoko; Tagne, Anselme Junior; Ngnie, Gaelle; Dedzo, Gustave Kenne; Ngameni, Emmanuel
Abstract : Successful chemical and electrochemical catalytic reduction of 4-chloro-2-nitroaniline onto palladium nanoparticle supported organo-kaolinite. Abstract : Palladium nanoparticle (PdNP) supported organo-kaolinite was used as a solid catalyst for the reduction and electrochemical detection of 4-chloro-2-nitroaniline (CNA). During the catalytic reduction in the presence of NaBH4, the effects of some essential experimental parameters were scrutinized. The rate of the reaction increases when the CNA concentration is decreased, while an increase in NaBH4 and catalyst concentration favored the reaction. The presence of a small amount of ascorbic acid (AA), used as an eco-friendly reducing agent, significantly increases the rate of the reaction. This increase was the consequence of the direct generation of dihydrogen, which accelerates the reaction by favoring the homogenization of the reaction medium. Despite the fact that the signal of CNA on an electrode modified by the catalyst was poorly reproducible, reduction of the nitro group occurs at a more favourable potential and the oxidation of the product of this reaction was catalyzed by evolved hydrogen following water reduction onto PdNPs. This phenomenon was marked by an irreversible signal 40 times higher, compared to the signal recorded in the absence of the catalyst at the gold electrode. This property can be firstly exploited for the detection of CNA at trace levels in an aqueous medium and secondly for the selective detection of nitroaromatic compounds and their metabolites.